Analysis of the clinical characteristics and treatment needs of patients with atopic dermatitis - Jinping YUAN; Jiaying LIN; Bingxue BAI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To explore the clinical characteristics, the disease disturbance and the treatment needs of patients with atopic dermatitis. Methods We retrospectively analyzed the data of patients with atopic dermatitis who completed the disease management manual for atopic dermatitis at the department of dermatology of the Second Affiliated Hospital of Harbin Medical University from June 2022 to June 2023. The analyses included demographic characteristics, ADCT score, treatment and laboratory test results. Results A total of 119 patients with AD were included in this analysis. The most common involved body site is the upper arms. In the real world, 95.52% of the patients considered that both pruritus and skin lesions affected the quality of their lives and were the main disease trouble. Long-term control of disease and decrease recurrence were expected by 94.67% of the patients. Patients treated with topical glucocorticoids or calcineurin inhibitors accounted for 93.58%, while 85.32% of patients were treated with oral anti-histamines. Disease was poorly controlled in 60.50% of patients in the real world (ADCT ≥7). The patients with long history of disease (>3 years) have higher ADCT scores than the patients with shorter history of disease (≤3 years) (Z=2.41, P=0.016). Conclusions In the real world, patients expect long-term control of the disease. Improper treatment can result in poor disease control in patients with atopic dermatitis.